2018
DOI: 10.1108/par-01-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial leverage on profitability of listed manufacturing firms in China

Abstract: Purpose The purpose of the study is to explore how financial leverage influences profitability of 1,503 listed manufacturing firms in China. Design/methodology/approach The sample of the study is composed of the listed manufacturing firms in China. For the manufacturing firms, the annual financial information from 2008 to 2016 is obtained from the ORBIS database. In this study, initially a simultaneous equation approach is used to control for potential endogeneity. Then, additional regression analyses are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
71
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 119 publications
15
71
0
8
Order By: Relevance
“…The results of this study are in accordance with Dalci's (2018) study of the focus of previous manufacturing companies in China; Dimitriae et al (2019) focused on hotel companies in several Mediterranean countries; Das and Swain (2018) focus on 50 manufacturing companies in India; Nhung and Okuda (2015) focus on companies on the Exchange in Vietnam and Vãtavu (2015) focus on companies on the Romanian Stock Exchange. Their research documents that debt affects company performance.…”
Section: Effect Of Debt To Equity Ratio On the Financial Performancesupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study are in accordance with Dalci's (2018) study of the focus of previous manufacturing companies in China; Dimitriae et al (2019) focused on hotel companies in several Mediterranean countries; Das and Swain (2018) focus on 50 manufacturing companies in India; Nhung and Okuda (2015) focus on companies on the Exchange in Vietnam and Vãtavu (2015) focus on companies on the Romanian Stock Exchange. Their research documents that debt affects company performance.…”
Section: Effect Of Debt To Equity Ratio On the Financial Performancesupporting
confidence: 83%
“…That means that companies in Romania are not profitable enough only to use internal funds for their investments. Research by Dalci (2018) on the hotel industry in the Mediterranean country found that factors affecting profitability are not the same in every coun-try. For instance, leverage affects profitability in hotel companies except for those in Greece.…”
mentioning
confidence: 99%
“…Pro tability is a measurement of e ciency and success or failure. In the context of some prior work (Dalci 2018, (Evgeny 2015 (lavorskyi 2013) explained pro tability have signi cant in uence on debt level. Similarly pro t have a positive connection between LD (β = 0.783, p < 0.000) and SD (β = 0.824, p < 0.000) TA (tangible assets) have signi cant positive association with debt level under GMM (β = 0.452, p < 0.014) Tangible assets are more important to business because they show company's worth.…”
Section: Discussionmentioning
confidence: 87%
“…The trade-off theory predicts a positive association between capital structure and firm performance. In support with this, several empirical studies found a positive relationship between capital structure and firm performance (e.g., Dalci, 2018;Berger and di Patti, 2006;Abor, 2005;Ghosh et al, 2000;Hadlock and James, 2002). The pecking order theory expects that the association between capital structure and firm performance is negative.…”
Section: Introductionmentioning
confidence: 85%
“…The extant research on the association of capital structure with firm performance provided mixed and contradictory results. Several studies reported a positive relationship between capital structure and firm performance (Dalci, 2018;Berger and di Patti, 2006;Abor, 2005;Hadlock and James, 2002;Ghosh et al, 2000;Champion, 1999;Roden and Lewellen, 1995;Ross, 1977). Conversely, some studies reported a negative association between capital structure and firm performance (Fernández-Temprano and Tejerina-Gaite, 2020; Assenga et al, 2018;Mishra and Kapil, 2017;Yasser et al, 2017;Plalniappan, 2017;Vithessonthi and Tongurai, 2015;Kumar and Singh, 2013;Sheikh and Wang, 2012;Cai and Zhang, 2011;Cheng, 2009;Ebaid, 2009;Jermias, 2008;Antoniou et al, 2008;Tian and Zeitun, 2007;Joshua, 2007;Haniffa and Hudaib, 2006;Weir et al, 2002;Fama and French, 2002;Booth et al, 2001;Gleason et al, 2000;Milton and Raviv, 1991;Short and Keasey, 1999;Majumdar and Chhibber, 1999;Wald, 1999;Kinsman and Newman, 1998;McConnell and Servaes, 1995;Rajan and Zingales, 1995;Friend and Lang, 1988;Kester, 1986;Titman and Wessels, 1988).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%